PENGEMBANGAN BUKU AJAR TEMATIK KELAS IV BERBASIS INTEGRASI ISLAM PADA SUBTEMA PEMANFAATAN ENERGI DI SEKOLAH DASAR - Muhammad Walid; Nur Hidayah Hanifah (JMIE (Journal of Madrasah Ibtidaiyah Education), 2017)
The development of thematic teaching book with subtheme energy utilization is one of the facilities to help students understand during learning process. By using teaching book, the purpose is to motivate and initiate the creativity of the students, and an effort to form their habit to work hard in order to gain knowledge, without teacher’s assistance. The teaching book to support the learning process with subtheme energy utilization is Islam-integration-based teaching book, in the form of teaching book for IV grader of elementary school.Product specification resulting from research and development is to produce a textbook integration of Islam based thematic sub-themes of energy utilization. Textbooks thematic sub-themes of energy in it presses right on the breadth of material content and concept of learning so that students can better understand the lesson. In addition to emphasis the concept, teaching materials fitted with the integration of Islam and the end of each lesson there is a verse of the Qur'an that can foster a love of students of the Qur'an.The result of the study has validity criteria score from the material expert is 94%, media expert is 90%, subject expert is 94&, and the result of the field testing is 92%. The students’ average score for the pre-test is 71 and for the post-test is 91. In manual t-test with significance level 0,05, the result shows that t hitung ≥ t tabel is 3,891015 ≥ 1,701, means that Ho is rejected and Ha accepted. Thus, it shows that there is significant difference toward the teaching book which is developed. It shows that the developed product has high validation level of qualification, means that the book is appropriate to be used in learning processes.